Method for preparing porous carbon electrode material by ordered assembly of oxygen-rich heavy oil activation step

CN122748645APending Publication Date: 2026-09-15SOUTHEAST UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610871028.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-16
Publication Date
2026-09-15

AI Technical Summary

Technical Problem

(1)传统碳源来源单一,制备过程依赖不可再生资源,不利于绿色低碳发展;

Benefits of technology

本发明提供了一种富氧重油有序组装梯级活化制备多孔碳电极材料的方法,该方法通过镁离子桥联组装作用实现前驱体分子有序构筑,提高碳收率和结构稳定性;并利用草酸盐梯级活化构建微孔-介孔协同分布的多级孔结构,实现离子快速扩散和高效储存;通过含氮草酸盐同步掺杂构筑丰富氮活性位点和缺陷结构,提高材料导电性及离子吸附能力。本发明方法的制备过程无需使用强腐蚀性活化剂,具有绿色环保、工艺简单和易于规模化生产等优点,实现了废弃富氧重油资源的高值化利用,提高了生物质热解副产物的附加值。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122748645A_ABST
    Figure CN122748645A_ABST
Patent Text Reader

Abstract

The application discloses a method for preparing porous carbon electrode material by ordered assembly and stepwise activation of oxygen-rich heavy oil, and belongs to the field of high-value utilization of biomass resources and preparation of energy storage materials. The method is characterized by the following steps: firstly, a bridging assembly-stepwise etching-defect regulation strategy is adopted; secondly, oxygen-rich heavy oil is used as a carbon source; thirdly, magnesium salt is used to induce the ordered assembly of a precursor; and fourthly, oxalate is pyrolyzed to realize stepwise activation and pore formation, and nitrogen-doped defect sites are simultaneously constructed by using nitrogen-containing oxalate. The obtained carbon material forms a through multi-level pore network and rich surface active sites, has high specific surface area, high pore volume and excellent ion transmission performance, and can promote the ion adsorption / desorption process through the pore size effect and surface charge driving effect, thereby effectively solving the problems of disordered pore structure and insufficient active sites in the existing oxygen-rich heavy oil carbonization process, realizing the directional conversion of waste oxygen-rich heavy oil into high-value energy storage carbon material, and being applicable to supercapacitors, zinc ion hybrid capacitors and other aqueous energy storage devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the high-value utilization of biomass resources and the preparation of energy storage materials, and particularly to a method for preparing porous carbon electrode materials by orderly assembly and stepwise activation of oxygen-enriched heavy oil. Background Technology

[0002] With the continued growth of global energy demand and the increasingly prominent environmental problems caused by the overconsumption of fossil fuels, the development of high-performance, low-cost, and green sustainable electrochemical energy storage materials has become an important research direction in the energy field. Supercapacitors, zinc-ion hybrid capacitors, and other aqueous energy storage devices have attracted widespread attention due to their advantages such as high power density, long cycle life, good safety, and environmental friendliness. Among them, carbon-based electrode materials are considered one of the most promising energy storage electrode materials due to their excellent conductivity, high chemical stability, wide availability of raw materials, and low cost.

[0003] Currently, porous carbon materials mainly originate from carbon sources such as coal, petroleum coke, and biochar, and achieve high specific surface areas after chemical or physical activation. However, existing technologies still have the following problems: (1) Traditional carbon sources are singular and the preparation process relies on non-renewable resources, which is not conducive to green and low-carbon development; (2) Most existing activation methods use strong corrosive activators such as potassium hydroxide and zinc chloride, which have problems such as serious equipment corrosion, high risk of environmental pollution and complicated post-processing. (3) Conventional activation processes mainly focus on increasing specific surface area, but lack precise control over pore structure, which easily leads to the formation of a large number of ineffective micropores and restricts the rapid transport of electrolyte ions; (4) The number of active sites on the surface of carbon materials is limited and the ion adsorption capacity is insufficient, which makes it difficult to further improve the specific capacity and rate performance; (5) The large amount of oxygen-rich heavy oil produced during biomass pyrolysis is usually treated as a low-value-added fuel for direct combustion due to its complex composition, high oxygen content and poor stability, and has failed to achieve its high-value utilization.

[0004] Oxygen-enriched heavy oil is an important liquid product of biomass pyrolysis. It contains abundant phenols, aldehydes, ketones, acids, and oxygen-containing aromatic compounds, possessing rich active functional groups and a high carbon content, making it a potentially high-quality precursor for the preparation of functional carbon materials. However, due to its complex molecular composition and poor thermal stability, oxygen-enriched heavy oil is prone to disordered polymerization and volatilization losses during traditional pyrolysis, resulting in low carbon yield and uncontrollable pore structure, severely limiting its application in the preparation of high-performance carbon materials.

[0005] In recent years, researchers have attempted to control the structure of carbon materials using strategies such as template methods, chemical activation methods, and heteroatomic doping. However, most studies focus only on optimizing single structural parameters, making it difficult to achieve synergistic control over precursor molecule assembly, pore structure construction, and surface active site regulation. Therefore, developing a novel preparation method capable of achieving directional conversion of oxygen-enriched heavy oil, precise pore structure regulation, and synergistic construction of defective active sites is of great significance for promoting the high-value utilization of waste biomass resources and the development of high-performance energy storage materials. Summary of the Invention

[0006] In view of the above-mentioned deficiencies in the prior art, the purpose of this invention is to provide a method for preparing porous carbon electrode materials by ordered assembly and stepwise activation of oxygen-enriched heavy oil. This method uses biomass-derived oxygen-enriched heavy oil as a carbon source, and through the synergistic effects of magnesium salt bridging assembly, oxalate stepwise activation, and nitrogen-containing oxalate defect regulation, achieves the efficient conversion of oxygen-enriched heavy oil into porous carbon materials with high specific surface area, high pore volume, and high active site density, thereby obtaining nitrogen-doped porous carbon electrode materials with excellent electrochemical energy storage performance.

[0007] To achieve the above objectives, the technical solution provided by the present invention is as follows: In a first aspect of the present invention, a method for preparing porous carbon electrode materials by ordered assembly and stepwise activation of oxygen-enriched heavy oil is provided, comprising the following steps: (1) Mix oxygen-rich heavy oil, magnesium salt activator, oxalate activator and nitrogen-containing oxalate dopant to obtain a homogeneous composite precursor; (2) The composite precursor is prepolymerized to form a bridged coordination structure between the phenolic hydroxyl groups, carbonyl groups, ether bonds and aromatic structural units in the reoxygenated heavy oil and magnesium ions to obtain a thermal conversion precursor. (3) The thermal conversion precursor is subjected to thermal conversion treatment under an inert atmosphere. During the thermal conversion process, the oxygen-rich heavy oil undergoes bridging polymerization, aromatization condensation and synchronous activation reaction. The magnesium salt activator promotes the orderly assembly between oxygen-rich heavy oil molecules and forms a spatially confined structure. The oxalate activator decomposes and releases active gas to perform stepwise etching and pore creation on the carbon skeleton. Nitrogen-containing oxalate simultaneously completes nitrogen element doping. (4) After the thermal conversion treatment is completed, the solid is cooled to room temperature and then subjected to acid washing, water washing and drying to obtain porous carbon electrode material.

[0008] Oxygen-enriched heavy oil is a bottom-layer enriched component during the pyrolysis and condensation process of biomass. It contains a large amount of phenols, aldehydes, ketones, acids, and oxygen-containing aromatic compounds, and has abundant active functional groups and a high carbon content. The sources of oxygen-enriched heavy oil in this invention are diverse and not specifically limited. For example, at least one of the following commonly used oxygen-enriched heavy oils in the field—pine wood pyrolysis, rice husk pyrolysis, lignin pyrolysis, and agricultural and forestry waste pyrolysis—can be used as raw materials for this process.

[0009] Preferably, in step (1), the magnesium salt activator includes one or more of magnesium chloride, magnesium nitrate, magnesium acetate, magnesium carbonate, and magnesium sulfate.

[0010] Preferably, in step (1), the oxalate activator includes one or more of potassium oxalate, sodium oxalate, and calcium oxalate.

[0011] Preferably, in step (1), the nitrogen-containing oxalate dopant includes one or more of ammonium oxalate, ammonium hydrogen oxalate, and ammonium tetraoxalate.

[0012] Preferably, in step (1), the mass ratio of the oxygen-enriched heavy oil, magnesium salt activator, oxalate activator and nitrogen-containing oxalate dopant is 10:(1~8):(5~20):(0.5~5).

[0013] Preferably, in step (2), the temperature of the prepolymerization treatment is 80~120 ℃ and the treatment time is 1~6 h.

[0014] Preferably, in step (3), the heating rate of the thermal conversion treatment is 2~20 ℃ / min, the treatment temperature is 600~1000 ℃, and the holding time is 0.5~4 h.

[0015] The stepwise activation of this invention is completed during the thermal conversion process. Magnesium salts form magnesium oxide nanoparticles in situ during thermal conversion, which act as hard templates to promote mesoporous formation. After heat treatment, the magnesium oxide can be removed by acid washing, thereby obtaining a continuous mesoporous structure. Oxalates, through thermal decomposition, release carbon monoxide and carbon dioxide, which react with the carbon skeleton in a gas-solid reaction to etch micropores, forming a rich microporous structure. This microporous structure, together with the template-induced mesoporous structure, constructs a multi-level pore system. Nitrogen-containing oxalates form surface active sites rich in pyridine nitrogen, pyrrole nitrogen, and graphitic nitrogen during pyrolysis, and induce the formation of defects in the carbon skeleton, thereby enhancing the material's ion adsorption and charge transfer capabilities. During the thermal conversion process, the inert atmosphere can be created by nitrogen, argon, or a mixture thereof; those skilled in the art can select the appropriate type or combination based on actual conditions.

[0016] Preferably, in step (4), the pickling is performed using hydrochloric acid, nitric acid, sulfuric acid or a mixture thereof; the acid concentration is 0.01~2 mol / L.

[0017] In a second aspect of the invention, a porous carbon electrode material is provided, which is manufactured using the method of the first aspect of the invention.

[0018] Preferably, the porous carbon material has a micropore-mesopore synergistic distribution structure with a pore size distribution in the range of 0.5~5 nm.

[0019] Preferably, the specific surface area of ​​the porous carbon material is 1000~3000 m². 2 / g; total pore volume is 0.5~2.5 cm³. 3 / g; mesoporous volume fraction of 20%~60%; nitrogen content of 0.5 wt.%~10 wt.%, of which the total proportion of pyridine nitrogen and pyrrole nitrogen is ≥50%.

[0020] In a third aspect of the invention, the application of the porous carbon electrode material of the second aspect of the invention in energy storage devices is provided.

[0021] Porous carbon electrode materials possess characteristics such as high specific surface area, hierarchical pore structure, high defect density, and abundant nitrogen functional groups, which can effectively improve ion transport efficiency, charge storage capacity, and cycle stability. In applications, porous carbon electrode materials synergistically promote ion adsorption / desorption processes through pore sieving effect and surface charge-driven effect, significantly improving ion diffusion rate and energy storage efficiency. Applicable energy storage devices include supercapacitors, zinc-ion hybrid capacitors, potassium-ion capacitors, and aqueous ion energy storage devices.

[0022] Based on the above technical solutions, the design concept and principle of this invention are as follows: In this field, oxygen-enriched heavy oil originates from the bottom-layer enriched components during the condensation of biomass pyrolysis. It is characterized by complex composition, high content of oxygen-containing functional groups, poor thermal stability, high volatility, and tendency for disordered polymerization. Based on these characteristics, the physicochemical properties of oxygen-enriched heavy oil differ significantly from those of ordinary bio-oils or general carbon sources in this field. Furthermore, oxygen-enriched heavy oil struggles to form a stable and controllable carbon framework during traditional pyrolysis processes.

[0023] To address the specific technical problems mentioned above, this invention proposes for the first time a synergistic construction mechanism of "bridging assembly - step-by-step etching - defect optimization". Specifically, magnesium ions coordinate with oxygen-containing functional groups such as phenolic hydroxyl groups, carbonyl groups, and ether bonds in oxygen-rich heavy oil, inducing precursor molecules to form an ordered bridging assembly structure. During thermal conversion, oxalate gradually decomposes to release carbon monoxide and carbon dioxide gases, performing step-by-step etching on the carbon skeleton to construct a hierarchical porous structure with a synergistic distribution of micropores and mesopores. Nitrogen-containing oxalate simultaneously releases nitrogen-containing active components during pyrolysis, constructing abundant pyridine nitrogen, pyrrole nitrogen, and defect active sites on the carbon skeleton surface, thereby achieving simultaneous optimization of the pore structure and surface chemical structure.

[0024] Specifically, this invention first designs a magnesium ion bridging assembly strategy for the special system of oxygen-enriched heavy oil. By utilizing the coordination between magnesium ions and oxygen-containing functional groups such as phenolic hydroxyl groups and carbonyl groups, ordered assembly at the molecular level is achieved before pyrolysis, thereby solving the problem of disorder in the carbonization process of oxygen-enriched heavy oil.

[0025] In this invention, the magnesium salt is not merely used as a template agent. Magnesium ions first participate in bridging assembly to form an ordered precursor, and then, during thermal conversion, uniformly dispersed magnesium oxide nanoparticles are formed in situ, creating a spatially confined environment. Based on this, the carbon monoxide and carbon dioxide released from the decomposition of oxalate are not randomly etched in an open system, but rather directionally and stepwise etched onto the carbon framework within the confined space formed by the magnesium oxide, thereby achieving simultaneous coordination between mesopore construction and micropore generation. The resulting micropore-mesopore interconnected structure cannot be obtained solely through template action or activation.

[0026] Nitrogen-containing oxalates are not used as a simple nitrogen source. This invention utilizes the nitrogen-containing active species generated during their pyrolysis to complete in-situ doping while the carbon framework is etched and the new surface is exposed, thereby forming active sites such as pyridine nitrogen, pyrrole nitrogen, and graphitic nitrogen. In other words, defect formation, pore structure evolution, and nitrogen doping occur simultaneously in the same thermal conversion stage, rather than the "pore formation first, doping later" or "activation and doping are independent" modes commonly found in existing technologies.

[0027] Based on the above design, this invention fundamentally solves the problem of the difficulty in synergistically controlling the assembly of precursor molecules, the construction of pore structures, and the formation of surface active sites in oxygen-rich heavy oil systems, rather than simply increasing the specific surface area or nitrogen content. The three activators influence and promote each other during the same thermal conversion process, jointly driving structural evolution. Therefore, the final product is a carbon material system with interconnected multi-level pores, high-density active nitrogen sites, and optimized electronic structure. This collectively solves the technical challenge of synergistically controlling the assembly of precursor molecules, the construction of pore structures, and the regulation of surface active sites.

[0028] It should be noted that the inventors' team used rice husk bio-oil as the carbon source, magnesium chloride as the template agent, and potassium oxalate as the activator to prepare graded porous carbon in the research literature (Zhu Wei, Qi Penggang, Su Yinhai, et al. Preparation and performance of graded porous carbon supercapacitor electrode materials based on bio-oil[J]. Chemical Industry and Engineering Progress, 2023, 42(6):3077-3086. DOI:10.16085 / j.issn. 1000-6613. 2022-1517.). This process is based on the combined use of template agent and oxalate activation, and the resulting porous carbon material has high specific surface area, high mesoporosity, and excellent electrochemical performance. Compared with oxygen-enriched heavy oil, rice husk bio-oil has fewer oxygen-containing active groups and lacks bridging coordination conditions. Its physicochemical properties are very different from those of oxygen-enriched heavy oil, and it cannot be regarded as a precursor of the same type. Secondly, the technical approach of that literature mainly focuses on improving specific surface area and mesoporous ratio by utilizing magnesium salt templates and oxalate activation, with an emphasis on pore structure control. No nitrogen doping is performed throughout the process, and performance improvement relies on double-layer capacitance. This invention, however, utilizes nitrogen-containing oxalate to simultaneously achieve activation, nitrogen doping, and defect control. The nitrogen-doped active sites provide considerable pseudocapacitance, resulting in a material with a specific capacitance far exceeding that of previous studies. The research literature does not present the synergistic system of bridging assembly, cascade activation, and defect control coupled in this invention.

[0029] Furthermore, existing processes, such as those described in the literature (Wang Caiwei. Structural Regulation and Lithium / Potassium Storage Performance of Lignin Carbon Materials by Oxalate [D]. South China University of Technology, 2023.), utilize the gas-phase exfoliation effect generated by the thermal decomposition of oxalate to regulate the microstructure and electrochemical properties of carbon materials. However, existing methods mainly involve solid-solid mixing of lignin solid raw materials with potassium oxalate activator. During pyrolysis, potassium oxalate only etches the surface of the lignin carbon shell, resulting in carbon materials with a small specific surface area. In contrast, this invention selects potassium oxalate based on its solubility in heavy oils. Building upon the ordered carbon precursor formed by bridging assembly, it achieves the synergistic construction of micropores and transport mesopores through the induction of mesopore formation by magnesium oxide template and the induction of micropore formation by gas etching from the thermal decomposition of oxalate. In this thermal conversion process, potassium oxalate can etch the carbon skeleton from point to surface and from inside to outside, resulting in carbon materials with more uniform pores and a larger specific surface area. Both methods use the same raw materials but have different design concepts.

[0030] Constructing porous carbon using magnesium chloride or magnesium hydroxide to form magnesium oxide hard templates in situ is a known technique in the field (Singh G, Kunjumon J, Kaur H, et al. Nanoarchitectonics of Porous Carbons Templated by Inorganic Metal Oxides and Alkali Metal Salts for Energy and Environmental Applications. Advanced Science (Weinheim, Baden-wurttemberg, Germany). 2026 May;13 (30):e17776. DOI: 10.1002 / advs.202517776. PMID:41887934.). Existing techniques only utilize magnesium oxide templates in the high-temperature carbonization stage, while as described above in the design of this invention, this invention utilizes magnesium ions to achieve oxygen-containing molecular bridging coordination in the low-temperature precursor construction stage. In this invention, magnesium salts are not simply used as template agents. Magnesium ions have the dual functions of inducing molecular assembly and setting pore structures, and are based on a joint assembly strategy to fully utilize the advantages of oxygen-containing functional groups in the raw materials.

[0031] In the simultaneous application of potassium oxalate and nitrogen doping, the academic paper (Liu Zhaomei. Preparation of Ultra-High Specific Surface Area Porous Carbon Materials and Research on Their Supercapacitor Performance [D]. Zhejiang Normal University) uses a synergistic method of potassium oxalate activation and urea nitrogen doping to prepare nitrogen-doped porous carbon with ultra-high specific surface area. The main purpose of this type of technical solution is to improve the conductivity and pseudocapacitive contribution of carbon materials, but the nitrogen doping sites provided by nitrogen-containing compounds are difficult to directionally control. Unlike simple nitrogen doping, this invention uses nitrogen-containing oxalate, in which oxalate ions can simultaneously achieve pore formation, nitrogen doping, and defect control, precisely control nitrogen active sites, and combine multi-level channels to synergistically optimize ion transport.

[0032] Compared with the prior art, the present invention has the following advantages and beneficial effects: This invention provides a method for preparing porous carbon electrode materials through ordered assembly and stepwise activation of oxygen-enriched heavy oil. This method achieves ordered molecular construction of precursors through magnesium ion bridging, improving carbon yield and structural stability. Furthermore, it utilizes oxalate stepwise activation to construct a hierarchical porous structure with a synergistic distribution of micropores and mesopores, enabling rapid ion diffusion and efficient storage. Simultaneous doping with nitrogen-containing oxalate constructs abundant nitrogen-active sites and defect structures, enhancing the material's conductivity and ion adsorption capacity. The preparation process of this invention does not require the use of highly corrosive activators, offering advantages such as being environmentally friendly, simple, and easy to scale up, thus realizing the high-value utilization of waste oxygen-enriched heavy oil resources and increasing the added value of biomass pyrolysis byproducts.

[0033] This invention provides a porous carbon electrode material with high specific surface area, hierarchical pore structure, high defect density and abundant nitrogen functional groups, which can effectively improve ion transport efficiency, charge storage capacity and cycle stability.

[0034] This invention provides the application of porous carbon electrode materials in energy storage devices, which exhibit excellent specific capacity, rate performance and cycle stability in supercapacitors, zinc-ion hybrid capacitors and other aqueous energy storage devices, and have broad application prospects. Attached Figure Description

[0035] Figure 1 A scanning electron microscope image of a porous carbon electrode material; Figure 2 X-ray diffraction pattern of porous carbon electrode material; Figure 3 The nitrogen adsorption-desorption isotherm diagram for porous carbon electrode materials; Figure 4 A pore size distribution curve of a porous carbon electrode material; Figure 5 The fine spectrum curve of nitrogen element in X-ray photoelectron spectroscopy of porous carbon electrode material; Figure 6 The cyclic voltammetry test curves for porous carbon electrode materials are shown. Figure 7 The constant current charge-discharge test curves for porous carbon electrode materials; Figure 8 This is a summary graph of the specific capacitance of porous carbon electrode materials under different current densities. Detailed Implementation

[0036] The present invention is further illustrated below by way of embodiments, but the invention is not limited to the scope of the embodiments described herein. Experimental methods in the following embodiments that do not specify specific conditions were performed according to conventional methods and conditions, or as selected according to the product instructions.

[0037] In the following examples or comparative examples, the bottom liquid phase obtained by condensing pine sawdust after pyrolysis at 500 °C was selected as the oxygen-enriched heavy oil (HBO) feedstock.

[0038] Example 1 This embodiment provides a method for preparing porous carbon electrode materials by ordered assembly and step-by-step activation of oxygen-enriched heavy oil, the steps of which are as follows: (1) Weigh 10.0 g of oxygen-enriched heavy oil, 5.0 g of magnesium chloride (MgCl2), 10.0 g of potassium oxalate (K2C2O4) and 1.0 g of ammonium oxalate [(NH4)2C2O4], mix them thoroughly and stir for 30 min to form a homogeneous composite precursor; (2) The composite precursor is prepolymerized at 105 °C for 2 h to allow the phenolic hydroxyl groups, carbonyl groups, ether bonds and aromatic structural units in the reoxygenated heavy oil to form a bridged coordination structure with magnesium ions, thus obtaining the thermal conversion precursor. (3) The thermal conversion precursor was heated to 800 ℃ at 10 ℃ / min under a nitrogen atmosphere and held for 1 h to complete the thermal conversion treatment; (4) After the thermal conversion treatment is completed, the material is cooled to room temperature and soaked overnight in 0.1 mol / L hydrochloric acid. After washing with deionized water until neutral, it is dried at 105 °C for 12 h to obtain nitrogen-doped porous carbon electrode material, denoted as MK-NAC-1.

[0039] The obtained MK-NAC-1 has a specific surface area of ​​2239 m². 2 / g, forming a synergistic distribution structure of 0.73 nm and 1.18 nm micropores and about 2.0 nm mesopores; nitrogen is uniformly dispersed in the carbon skeleton, with pyridine nitrogen and pyrrole nitrogen accounting for a total of 69.66%.

[0040] Example 2 This embodiment provides a method for preparing porous carbon electrode materials by ordered assembly and step-by-step activation of oxygen-enriched heavy oil, the steps of which are as follows: (1) Weigh 10.0 g of oxygen-enriched heavy oil, 5.0 g of magnesium chloride (MgCl2), 10.0 g of potassium oxalate (K2C2O4) and 2.0 g of ammonium oxalate [(NH4)2C2O4], mix them thoroughly and stir for 30 min to form a homogeneous composite precursor; (2) The composite precursor is prepolymerized at 105 °C for 2 h to allow the phenolic hydroxyl groups, carbonyl groups, ether bonds and aromatic structural units in the reoxygenated heavy oil to form a bridged coordination structure with magnesium ions, thus obtaining the thermal conversion precursor. (3) The thermal conversion precursor was heated to 800 ℃ at 10 ℃ / min under a nitrogen atmosphere and held for 1 h to complete the thermal conversion treatment; (4) After the thermal conversion treatment is completed, the material is cooled to room temperature and soaked overnight in 0.1 mol / L hydrochloric acid. After washing with deionized water until neutral, it is dried at 105 °C for 12 h to obtain nitrogen-doped porous carbon electrode material, denoted as MK-NAC-2.

[0041] The obtained MK-NAC-2 has a specific surface area of ​​2184 m². 2 / g, forming a synergistic distribution structure of 0.73 nm and 1.18 nm micropores and approximately 2.0 nm mesopores. Nitrogen is uniformly dispersed in the carbon framework, with pyridine nitrogen and pyrrole nitrogen accounting for a total of 64.97%.

[0042] Example 3 This embodiment provides a method for preparing porous carbon electrode materials by ordered assembly and step-by-step activation of oxygen-enriched heavy oil, the steps of which are as follows: (1) Weigh 10.0 g of oxygen-enriched heavy oil, 5.0 g of magnesium chloride (MgCl2), 10.0 g of potassium oxalate (K2C2O4) and 3.0 g of ammonium oxalate [(NH4)2C2O4], mix them thoroughly and stir for 30 min to form a homogeneous composite precursor; (2) The composite precursor is prepolymerized at 105 °C for 2 h to allow the phenolic hydroxyl groups, carbonyl groups, ether bonds and aromatic structural units in the reoxygenated heavy oil to form a bridged coordination structure with magnesium ions, thus obtaining the thermal conversion precursor. (3) The thermal conversion precursor was heated to 800 ℃ at 10 ℃ / min under a nitrogen atmosphere and held for 1 h to complete the thermal conversion treatment; (4) After the thermal conversion treatment is completed, the material is cooled to room temperature and soaked overnight in 0.1 mol / L hydrochloric acid. After washing with deionized water until neutral, it is dried at 105 °C for 12 h to obtain nitrogen-doped porous carbon electrode material, denoted as MK-NAC-3.

[0043] The obtained MK-NAC-3 has a specific surface area of ​​2093 m². 2 / g, forming a synergistic distribution structure of 0.73 nm and 1.18 nm micropores and approximately 2.0 nm mesopores. Nitrogen is uniformly dispersed in the carbon framework, with pyridine nitrogen and pyrrole nitrogen accounting for a total of 66.55%.

[0044] The above embodiments present representative implementation methods of the present invention. Those skilled in the art can select other raw materials or suitable parameters within the preferred parameter range of the present invention according to actual needs or conditions, and can achieve the basic purpose of the present invention and complete the preparation of the corresponding porous carbon electrode material.

[0045] Comparative Example 1 This comparative example provides a method for preparing porous carbon electrode materials by ordered assembly and step-by-step activation of oxygen-enriched heavy oil, the steps of which are as follows: (1) Weigh 10.0 g of oxygen-enriched heavy oil and 10.0 g of potassium oxalate (K2C2O4) and mix them thoroughly. Stir for 30 min to form a uniform precursor. (2) The obtained precursor was prepolymerized in an oven at 105 °C for 2 h; (3) Place the pretreated precursor in a quartz boat, transfer it to a tube furnace, and purge it with high-purity nitrogen (99.999%) for 30 min to remove air; under continuous nitrogen protection, heat it to 800 ℃ at 10 ℃ / min and hold it for 1 h. (4) After naturally cooling to room temperature, the obtained solid was soaked in 0.1 mol / L hydrochloric acid solution overnight; after washing with deionized water until neutral, it was dried at 105 ℃ for 12 h to obtain porous carbon electrode material, denoted as K-AC.

[0046] The obtained K-AC mainly forms a porous structure dominated by 0.73 nm micropores, with a specific surface area reaching 1385 m². 2 / g, with a mesoporous content of 3.32%.

[0047] Comparative Example 2 This comparative example provides a method for preparing porous carbon electrode materials by ordered assembly and step-by-step activation of oxygen-enriched heavy oil, the steps of which are as follows: (1) Weigh 10.0 g of oxygen-enriched heavy oil, 5.0 g of magnesium chloride (MgCl2) and 10.0 g of potassium oxalate (K2C2O4), mix them thoroughly and stir for 30 min to form a homogeneous composite precursor; (2) The obtained precursor was prepolymerized at 105 °C for 2 h to allow magnesium ions to form a bridged coordination structure with the phenolic hydroxyl groups, carbonyl groups and ether bonds in the oxygen-rich heavy oil. (3) Heat to 800 ℃ at 10 ℃ / min under a nitrogen atmosphere and hold for 1 h; (4) After cooling, the magnesium oxide template was removed by washing with 0.1 mol / L hydrochloric acid; after washing until neutral, it was dried at 105 °C for 12 h to obtain a porous carbon electrode material, denoted as MK-AC.

[0048] The obtained MK-AC exhibits a synergistic distribution of micropores (0.73 nm and 1.18 nm) and mesopores (approximately 2.16 nm); its specific surface area reaches 2286 m². 2 / g, with mesoporous components accounting for more than 30%.

[0049] Test Example 1 This test example is used to characterize the microstructure, crystal structure, pore structure and surface chemical composition of the porous carbon electrode materials prepared in the examples and comparative examples.

[0050] The morphology of the samples obtained in the examples and comparative examples was observed using a cold field emission scanning electron microscope (SEM), and the test results are as follows: Figure 1 As shown. Figure 1 (a) is a scanning electron microscope image of the K-AC sample. As can be seen from the figure, a certain number of pore structures are formed on the surface of K-AC, but the overall pore distribution is relatively uneven and the surface is relatively dense. Figure 1 Images (b) through (e) are scanning electron microscope (SEM) images of samples MK-AC, MK-NAC-1, MK-NAC-2, and MK-NAC-3, respectively. Compared to K-AC, the introduction of magnesium chloride resulted in a distinctly irregular granular structure in all samples, with a rougher particle surface and numerous open pores. This indicates that magnesium ions, after participating in precursor assembly, can promote carbon framework reconstruction and pore structure development during thermal conversion. Figure 1 (f) is a high-magnification scanning electron microscope image of the MK-NAC-1 sample. As can be seen from the figure, its surface has a rich and uniform pore structure, forming a continuous open pore network, which is conducive to electrolyte wetting and rapid ion diffusion. The above results indicate that magnesium salt bridging assembly and oxalate stepwise activation can synergistically promote the formation of hierarchical porous structures.

[0051] The crystal structure of the samples obtained in the examples and comparative examples was analyzed using X-ray diffraction (XRD), and the results are as follows: Figure 2 As shown. By Figure 2 It can be seen that all samples exhibit two broad diffraction peaks around 24° and 43°, corresponding to the (002) and (100) crystal planes of the carbon material, respectively, indicating that the obtained materials all belong to typical amorphous carbon structures. Compared with K-AC, the (002) diffraction peak of the MK-AC and MK-NAC series samples is further broadened, indicating that magnesium chloride synergistic activation and nitrogen doping promote the degree of disorder in the carbon layer and form more structural defects and active sites. The test results show that the material obtained in this invention maintains a good conductive carbon framework and has a high defect density, which is beneficial for charge storage and ion adsorption.

[0052] Nitrogen adsorption-desorption tests were performed on the samples obtained in the examples and comparative examples using a fully automated specific surface area and pore structure analyzer. The results are as follows: Figure 3 and Figure 4 As shown. Figure 3 The figures show the nitrogen adsorption-desorption isotherms of the samples. All samples exhibit typical Type I and Type IV adsorption isotherm characteristics, indicating that the materials contain both abundant micropores and a certain number of mesopores. Figure 4The corresponding pore size distribution curves are shown. The results indicate that the main pore sizes of each sample are concentrated around 0.73 nm and 1.18 nm, while mesoporous structures in the 2–5 nm range also exist, forming a clear micropore-mesopore synergistic distribution characteristic. Among them, the number of mesopores in the MK-AC and MK-NAC series samples is significantly higher than that in K-AC, indicating that the magnesium oxide template formed during the thermal conversion of magnesium chloride can effectively promote mesopore formation. The introduction of an appropriate amount of ammonium oxalate further optimizes the pore structure, enabling the material to form a multi-scale pore system composed of ion-sieving micropores, energy storage micropores, and transport mesopores. These results demonstrate that the present invention constructs a continuous multi-level pore structure, which is beneficial for improving ion transport efficiency and charge storage capacity.

[0053] X-ray photoelectron spectroscopy (XPS) was used to analyze the elemental composition of the sample surface and the chemical state of nitrogen. The results are as follows: Figure 5 As shown in the figure. The test results show that obvious nitrogen signals were detected on the surface of all MK-NAC series samples, indicating that nitrogen doping was successfully achieved in ammonium oxalate during thermal conversion. High-resolution N1s spectra show that nitrogen in the samples mainly exists in the form of pyridine nitrogen (N-6), pyrrole nitrogen (N-5), graphitic nitrogen (NQ), and nitrogen oxides (NX). Among them, pyridine nitrogen and pyrrole nitrogen account for the main proportion of the total nitrogen content and can serve as active sites for electrolyte ion adsorption, improving the pseudocapacitance contribution and charge transfer ability of the material surface.

[0054] Based on the combined results of SEM, XRD, nitrogen adsorption-desorption and XPS analysis, it can be seen that the present invention achieves the directional transformation of oxygen-rich heavy oil into carbon materials with high specific surface area, hierarchical porous structure and nitrogen-rich active sites through magnesium salt bridging assembly, oxalate stepwise activation and nitrogen-containing oxalate defect regulation, providing a structural basis for its application in the field of energy storage electrodes.

[0055] The preferred embodiments of the present invention have been described in detail above. It should be understood that those skilled in the art can make numerous modifications and variations based on the concept of the present invention without creative effort. Therefore, all technical solutions that can be obtained by those skilled in the art based on the concept of the present invention through logical analysis, reasoning, or limited experimentation on the basis of existing technology should be within the scope of protection defined by the claims.

Claims

1. A method for preparing porous carbon electrode materials by ordered assembly and stepwise activation of oxygen-enriched heavy oil, characterized in that, Includes the following steps: (1) Mix oxygen-rich heavy oil, magnesium salt activator, oxalate activator and nitrogen-containing oxalate dopant to obtain a homogeneous composite precursor; (2) The composite precursor is prepolymerized to form a bridged coordination structure between the phenolic hydroxyl groups, carbonyl groups, ether bonds and aromatic structural units in the reoxygenated heavy oil and magnesium ions to obtain a thermal conversion precursor. (3) The thermal conversion precursor is subjected to thermal conversion treatment under an inert atmosphere. During the thermal conversion process, the oxygen-rich heavy oil undergoes bridging polymerization, aromatization condensation and synchronous activation reaction. The magnesium salt activator promotes the orderly assembly between oxygen-rich heavy oil molecules and forms a spatially confined structure. The oxalate activator decomposes and releases active gas to perform stepwise etching and pore creation on the carbon skeleton. Nitrogen-containing oxalate simultaneously completes nitrogen element doping. (4) After the thermal conversion treatment is completed, the solid is cooled to room temperature and then subjected to acid washing, water washing and drying to obtain porous carbon electrode material.

2. The method for preparing porous carbon electrode materials by ordered assembly and stepwise activation of oxygen-enriched heavy oil according to claim 1, characterized in that: In step (1), the magnesium salt activator includes one or more of magnesium chloride, magnesium nitrate, magnesium acetate, magnesium carbonate, and magnesium sulfate; the oxalate activator includes one or more of potassium oxalate, sodium oxalate, and calcium oxalate; and the nitrogen-containing oxalate dopant includes one or more of ammonium oxalate, ammonium hydrogen oxalate, and ammonium tetraoxalate.

3. The method for preparing porous carbon electrode materials by ordered assembly and stepwise activation of oxygen-enriched heavy oil according to claim 1, characterized in that: In step (1), the mass ratio of the oxygen-rich heavy oil, magnesium salt activator, oxalate activator and nitrogen-containing oxalate dopant is 10:(1~8):(5~20):(0.5~5).

4. The method for preparing porous carbon electrode materials by ordered assembly and stepwise activation of oxygen-enriched heavy oil according to claim 1, characterized in that: In step (2), the temperature of the prepolymerization treatment is 80~120 ℃ and the treatment time is 1~6 h.

5. The method for preparing porous carbon electrode materials by ordered assembly and stepwise activation of oxygen-enriched heavy oil according to claim 1, characterized in that: In step (3), the heating rate of the thermal conversion treatment is 2~20 ℃ / min, the treatment temperature is 600~1000 ℃, and the holding time is 0.5~4 h.

6. The method for preparing porous carbon electrode materials by ordered assembly and stepwise activation of oxygen-enriched heavy oil according to claim 1, characterized in that: In step (4), the pickling is performed using hydrochloric acid, nitric acid, sulfuric acid, or a mixture thereof; The acid concentration is 0.01~2 mol / L.

7. A porous carbon electrode material, characterized in that: It is made by the method described in any one of claims 1 to 6.

8. The porous carbon electrode material according to claim 7, characterized in that: The porous carbon material has a micropore-mesopore cooperative distribution structure with pore size ranging from 0.5 to 5 nm.

9. The porous carbon electrode material according to claim 7, characterized in that: The specific surface area of the porous carbon material is 1000-3000 m 2 / g; the total pore volume is 0.5-2.5 cm 3 / g; the mesopore volume fraction is 20%-60%; the nitrogen content is 0.5 wt.%-10 wt.%, wherein the total proportion of pyridine nitrogen and pyrrole nitrogen is ≥50%.

10. The application of a porous carbon electrode material as described in any one of claims 7 to 9 in an energy storage device.